Origami triboelectric nanogenerator with double-helical structure for environmental energy harvesting. (1st December 2020) - Wang, Ying; Wu, Yesheng; Liu, Qi; Wang, Xiaodong; Cao, Jie; Cheng, Guanggui; Zhang, Zhongqiang; Ding, Jianning; Li, Kai
Abstract: Triboelectric nanogenerators (TENGs) based on contact electrification and electrostatic induction have emerged as promising green and clean energy harvesting devices. Its most unique property is that it can harvest low-frequency waste mechanical energy from the environment to electricity with high conversion efficiency. To improve the output power of TENGs, a lot of efforts have been done on fabrication of textured contact surface which leads to higher fabrication cost. In this work, inspired by the origami technology, we have designed a novel double helix structure TENGs (dh-TENG) with low cost and ease fabricating process. The dh-TENG can switch from 2D to 3D freely and significantly improve the output performance of TENG. Several factors, such as the input frequency, resistive load together with various structural parameters, were systematically investigated; the working mechanism of the dh-TENG was studied by using the COMSOL software. The experimental results show that the maximum output power of the dh-TENG reaches 0.58 mW when the external load resistance is 20 MΩ, which can fully power electronic devices such as capacitors and LEDs. These findings provide useful guidance for optimizing the performance of dh-TENGs for practical applications in self-powered systems and portable mobile electronic products, especially on soft electronics and wearable electronics. Highlights: A dh-TENG based on origami technology is fabricated. The dh-TENG can change from 2D to 3D freely by using origami technology. The dh-TENG can harvest various energies from environment.